Dakwah dan Pemberdayaan: Strategi Pengembangan Masyarakat Islam Melalui Komunitas Tasawuf Underground terhadap Anak Punk dan Anak Jalanan - Putri Nabila, Nur Hana (Indonesian Journal for Social Responsibility, 2021)
Da'wah has a very large function and role in all aspects of human life. Da'wah in the development of Islamic society as a form of da'wah bilhal with processes and activities that lead to the welfare of the community. Da'wah seeks to raise awareness of bad behaviour and instill charity ma'ruf nahi munkar in society. One of the applications of da'wah in the development of Islamic society through an Underground Tasawuf community. In fact, there are not many preachers or religious experts who are capable of being present among punk and street children. In addition, preaching is not enough to only teach religious education, but also economic and social empowerment so that punk and street children can emigrate totally. Therefore, the type of research used is field research with a qualitative descriptive approach. Data sourced from primary data and secondary data. The result of this research is that there is a significant change in punk and street children after being educated through the Underground Tasawuf community.